1998
DOI: 10.1029/97wr02573
|View full text |Cite
|
Sign up to set email alerts
|

Data for Ashley River to test channel network and river basin heterogeneity concepts

Abstract: Abstract. To provide data to investigate hypotheses about the evolution of channel networks, specifically the optimal channel network concept, discharge and channel properties were measured at 336 sites in a 121 km 2 basin over a 5-day period of reasonably steady flows. The data are also suitable for investigating how discharge increases down river channels. The data collection was a major logistical exercise which involved 80 person-days in remote field locations. In the expectation that the data will be of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 11 publications
(7 reference statements)
0
22
0
Order By: Relevance
“…Real channel networks exhibit statistical variability in their topology, geometry (Veitzer and Gupta, 2000) and hydraulic geometry (Ibbitt, 1997;McKerchar et al, 1998). There is a long history of published literature in geomorphology that has been devoted to understanding this variability (Jarvis and Woldenberg, 1984).…”
Section: Geomorphologic Analysismentioning
confidence: 99%
“…Real channel networks exhibit statistical variability in their topology, geometry (Veitzer and Gupta, 2000) and hydraulic geometry (Ibbitt, 1997;McKerchar et al, 1998). There is a long history of published literature in geomorphology that has been devoted to understanding this variability (Jarvis and Woldenberg, 1984).…”
Section: Geomorphologic Analysismentioning
confidence: 99%
“…OCNs have been analytically shown to produce three universality classes in terms of scaling exponents, but none of these predictions agrees with the data (Maritan et al, 1996). Two comprehensive field programs were carried out in New Zealand (NZ) to test the OCN predictions McKerchar et al, 1998). However, the observed values of the H-G exponents substantially deviated from the OCN predictions that is explained in greater detail in Sects.…”
Section: Background and Methodsmentioning
confidence: 84%
“…In making this plot, the theoretical condition − ω → ∞ is incorporated by omitting order 6 and 5 streams from the analysis. Mantilla (2014) found that the basin has a large number of the 1st order streams that are mostly missed in the map that McKerchar et al (1998) presented. Therefore, the Horton plot is made for streams of order ω = 2, 3, 4, shown in Fig.…”
Section: Test Of Horton Laws and The R Q = R A Relationship For The Amentioning
confidence: 99%
See 1 more Smart Citation
“…Flood statistics [1][2][3][4][5], water storage [6], drainage basin organization [7], relationships between channel dimensions and flow [8], extreme precipitation events [9], wind and weather fluctuations [10,11], stock and commodity markets fluctuations [12,13] , have all been noted to obey various power laws. Many physicists have searched for unifying concepts to explain such ubiquity.…”
mentioning
confidence: 99%